Determination of ginsenoside Rh3 in rat plasma by LC–MS/MS and its application to a pharmacokinetic study. (24th November 2021) - Yang, Ting; Xu, Wenwu; Wei, Xiyu; Zhang, Zhenzhen; Sun, Yue; Liu, Houru; Yu, Peihua; Li, Wei; Yu, Dehong
Abstract: Ginsenoside Rh3 (GRh3) is a bacterial metabolite of ginsenoside Rg5, which is the main component of hot‐processed ginseng. A simple, efficient and sensitive method was developed and validated for the determination of GRh3 in rat plasma by LC–tandem mass spectrometry. After protein precipitation with methanol/acetonitrile (1:1, vol/vol) using propranolol as the internal standard, the target analytes were separated on an XDB C18 column, with methanol containing 0.1% formic acid and water containing 0.1% formic acid used as mobile phases for gradient elution. Mass spectrometry was performed in electrospray ion source–positive ion mode and multiple reaction monitoring mode, monitoring the transitions m/z 622.5 → 425.5 and m/z 260.1 → 116.1 for GRh3 and internal standard, respectively. The concentration range of GRh3 was 20–20, 000 ng/mL and the correlation coefficient (r 2 ) was greater than 0.99. The accuracy error and relative standard deviation were below 15%. The extraction recovery and matrix effect were 74.2% to 78.7% and 96.9% to 108.4%, respectively. Under different conditions, GRh3 was stable in the range of 1.8%–8.7%. This method has been successfully applied to study the pharmacokinetics of GRh3 with an oral dose of 10.0 mg/kg and an intravenous dose of 2.0 mg/kg in rats, respectively. The absolute bioavailability of GRh3 was 37.6%.